Factors Affecting Households’ Electricity-Saving Behaviour: A Perspective on Sustainable Development - Vuong, Tuan Khanh (International Journal of Energy Economics and Policy, 2024)
As technology continues to advance, the demand for electricity increases, and resources become scarcer, awareness of energy saving and related issues is increasingly important and has been the focus of scholarly research in recent times. This study investigates the key factors influencing households’ electricity-saving behaviour in Ho Chi Minh City (HCMC), Vietnam, utilizing a convenience sampling approach. A total of 431 data samples were selected for examination. The research factors are attitude, social norms, personal moral norms, responsibility for energy-saving, degree of concern, policy, and social propaganda. These factors are expected to have an impact on perceived benefits and perceived behavioural control, which in turn are expected to positively influence the intention of HCMC householders to save electricity and engage in electricity-saving behaviours. The results show that all my hypotheses are accepted. This study identifies the key factors mentioned above that play important roles, as well as the two further factors of perceived benefits and perceived behavioural control, in shaping intentions for electricity-saving and the impact on electricity-saving behaviours. However, this study found that the degree of concern and policy and social propaganda do not significantly affect perceived benefit, contrary to the initial hypotheses. This study provides evidence and offers insights to policymakers regarding the key factors that influence households’ intentions to save electricity and their electricity-saving behaviours. Furthermore, this research lays the groundwork for scholars to develop a comprehensive understanding and conduct further in-depth studies aimed at proposing solutions to enhance awareness of electricity-saving among individuals and organisations. These efforts benefit the community and address environmental concerns, aligning with the UN’s Sustainable Development Goals.